COVID-19, Pregnant Women and Their Hard- Wired Worry - Shretha, Arati; Aryal, Shreyashi; Shresth, Deepak (Journal of Lumbini Medical College, 2020)
In our day to day obstetric practice, we face a number of concerns raised by the pregnant women regarding their health. Some of the frequently asked queries include: if they would develop health problems like high blood pressure and/or diabetes; if they would have a normal delivery or would require an intervention in the form of cesarean section or instrumentation, if they would have the birth experience as they envision and if the stress is harmful during the ongoing pregnancy. Every pregnant woman strives her best to give birth to a healthy child. As every pregnancy is a period of uncertainties and risks, pregnant women are anxious about their well-being and that of their baby. The list of concerns is endless with the addition of corona virus disease (COVID-19).